Perjanjian Yang Dilarang Berdasarkan Perspektif Hukum Persaingan Usaha Indonesia - Ghany Aziz, Kiagoos Haqqy Annafi (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2021)
Indonesia as a country has goals that have been agreed upon by all it’s people. One of the goals of the Indonesian state is to promote general welfare as mandated by the state constitution in the 1945 Constitution. In order to realize the country's goals, Indonesia must undertake development, especially in the economic sector with a populist economic system or economic democracy. Therefore, all forms of economic activity must be based on justice so that development in the economic sector can run conducive. One of the economic sectors that has a very large contribution is the business sector. The government has basically provided equal space or opportunity to all people to carry out business activities with fair competition. However, in practice, many agreements or business activities are found that do not reflect justice for business actors and society in general. In order to prevent and provide clear legal corridors, Indonesia enacted Law Number 5 of 1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition with the Business Competition Supervisory Commission (KPPU) as the implementer of the law. In this law it is regulated in detail and specifically regarding the forms of agreements prohibited in business competition, namely the agreements prohibited by Law No.5 of 1999 are oligopoly, price fixing, zoning, boycotts, cartels, trusts, oligopsony, and vertical integration, closed agreements and agreements with foreign parties, including therein are regulated regarding legal sanctions for those who violate, namely administrative sanctions and criminal sanctions.